Design of primers and probes for detection of influenza A and SARS-CoV-2 viruses RNA by real-time RT-PCR - Almezhanova, M.D.; Kozhabergenov, N.S.; Melisbek, A.M.; Shirinbekov, M.Zh.; Usserbayev, B.S.; Chervyakova, O.V.; Junushov, A.T.; Sultankulova, K.T. (NLC “Karaganda National Research University named after аcademician Ye.A. Buketov”, 2026)
Cost-effective, accurate, and rapid analysis is essential for testing and diagnosing both common and emerging viruses in clinical virology laboratories. In this study, we designed and selected oligonucleotides for the detection of influenza A virus and SARS-CoV-2 using real-time reverse transcription PCR (RT-qPCR). The development of domestic test systems for diagnosing influenza A virus and SARS-CoV-2 is an urgent task due to the need for early disease detection. The aim of this study is to select primers and probes for the diagnosis of influenza A and SARS-CoV-2 using reverse transcription PCR in real-time (RT-PCR RT). We present the results of designing primers and probes for the identification of influenza A and SARS-CoV-2 RNA. In our studies on the selection of specific primers and probes, the M gene was chosen as a target gene for detecting the influenza A virus, and the RdRp gene for the SARS-CoV-2 virus. A pair of oligonucleotide primers was selected and synthesized for influenza A InfM2 F and InfM2 R, as well as the InfM2 Probe, and for SARSCoV- 2 — RdRp-1 F and RdRp-2 R, the RdRp-2 Probe, which, when performing RT-PCR RT with a working concentration of 20 pmol showed high efficiency in detecting the influenza A virus and SARS-CoV-2. Primers were selected using the Primer Blast and Vector NTI computer programs. The designed primers and probes will be further used to create a domestic multiplex RT-PCR RT test system.
Нақты уақыттағы КТ-ПТР әдісі арқылы А тұмауы мен SARS-CoV-2 вирустарының РНҚ-ын анықтауға арналған праймерлер мен зондтарды таңдау
Подбор праймеров и зондов для выявления РНК вирусов гриппа А и SARS-CoV-2 методом ОТ-ПЦР в реальном времени
Keywords: influenza А; coronavirus; RT-PCR; diagnostics; test-system